O08.2 A national survey of canadians on hpv: comparing knowledge, barriers and preventive practices of physicians to those of consumers. (8th July 2017) - Steben, Marc; Blake, Jennifer; Durand, Nancy; Guichon, Juliet; Mcfaul, Susan; Ogilvie, Gina
Abstract : Introduction: This Canadian survey of physicians and consumers aimed to explore knowledge, barriers and preventive practices regarding HPV. Methods: We surveyed general practitioners (GPs) (n=337) and obstetrician/gynaecologists (OB/GYNs) (n=81); vaccinated (VW) (n=337) and unvaccinated 18–45 year old women (UW) (n=802), and 18–26 year old men (M) (n=200) in May and June 2016 using an online panel. A probability sample of the same size would yield a margin of error of +/-4.8% for physicians and +/-2.7% for consumers, 19 times out of 20. Two posters with more detailed individual information about both groups will be presented at the Cape Town, South Africa IPVS meeting in March 2017. Results: 83% GPs recommend or administer HPV vaccine to adults. 93%–98% of consumers said doctors are trustworthy sources of information. 99%–100% of physicians compared to VW (93%), UW (85%) and M (59%) somewhat or strongly agree that vaccination is an important aspect of disease prevention. A higher proportion of patients were concerned about vaccine safety (VW (26%), UW (40%) and M (36%)) than were physicians (5%–11%). 58%–61% of consumers were generally cautious about taking any vaccine. Cost was seen as a barrier by 92%–95% of physicians, however only 18%–20% of consumers considered cost a barrier. Consumers accurately answered a majority of questions about HPV, however physicians rated consumers' understanding of HPV to be low (11%–14% very good and 49%–56% somewhat good knowledge). VW (34%–31%) and VM (13%–31%) said physician recommendations/discussions did motivate them to be vaccinated. UW (55%–38%) and UM (57%–49%) said physician recommendations/discussions would motivate them to be vaccinated. 60%–66% of physicians say they routinely discuss HPV vaccination with patients. Conclusions: Some divergent views about HPV knowledge, barriers and preventive practices exist between physicians and consumers. These divergent views should be taken into account in consumer counselling and physician training.